GAM DAN ISU PELANGGARAN HAM DI ACEH: STUDI KASUS KONFLIK 1975-2005 - Nursaleha, Nursaleha (Education Enthusiast : Jurnal Pendidikan dan Keguruan, 2025)
This study analyzes the vertical conflict between the Free Aceh Movement (GAM) and the Indonesian central government in the period 1975-2005, covering the New Order era to the Reformation era. Using a qualitative approach and descriptive methods through observation techniques and library research, this study aims to examine the history of the formation of GAM, the dynamics of the vertical conflict in Aceh, the factors that drove the Acehnese people's desire to break away from Indonesia, and efforts to resolve the conflict to reach a peace agreement. The results of the study indicate that GAM was formed in response to the central government's centralistic policies, exploitation of natural resources, and marginalization of local political and cultural issues, with the conflict going through various phases of escalation until its peak in the Military Operations Area (DOM) period, which was then successfully resolved through international negotiation and mediation by signing the Helsinki Memorandum of Understanding (MoU) in 2005 as a peaceful solution that provides special autonomy for Aceh. Keywords: Conflict, GAM, New Orde